PENGGUNAAN METODE SOSIODRAMA UNTUK MELATIH KEMAMPUAN BERBICARA ANAK 5-6 TAHUN DI TK PRIMANDA UNTAN - Pipi, Margareta; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the used of the socio drama method to practice the speaking ability of children in the B1 group at TK Primanda Untan Pontianak. The research method used was descriptive with a qualitative research form. The data source of this research was the children of group B1 TK Primanda Untan. This research technique was observation with observation sheet, direct communication with interview sheet and documentary with documentation. Data analysis in this research was data collection, data reduction, presentation and conclusion / verification. The results of this study indicated that the used of the socio drama method to practice the accuracy of speech in children was appropriate in the used of sentences and belongs to the developing category as expected, the used of the socio drama method to train the placement of the interrogative sentence stress in children is in accordance with the sentence structure into the developing category according to expectations, the used the socio drama method to practice the placement of sentence stress statements in accordance with the proper sentence structure, the used of the socio drama method to practice the accuracy of word choices develops as expected, the used of the socio drama method to practice the accuracy of the target speech where the child speaks in accordance with the spoken sentence and used the sentence effectively. Based on the results of the study it is hoped that training and familiarizing children to use the sentence structure correctly.Â Keywords: Speaking ability, The use of socio drama